Molecular and cellular physiology of neurons - Fain, Gordon L.; O'Dell, Thomas, 1960- (Harvard University Press, 2014)
Molecular and Cellular Physiology of Neurons, Second Edition is a comprehensive, up-to-date introduction to essential concepts of cellular neuroscience. Emphasizing experimental approaches and recent discoveries, it provides an in-depth look at the structure and function of nerve cells, from protein receptors and synapses to the biochemical processes that drive the mammalian nervous system. Starting with the basics of electrical current flow across cell membranes, Gordon Fain covers voltage gating and receptor activation in the context of channel diversity, excitatory and inhibitory synaptic transmission, neuromodulation, and sensory transduction. Emphasizing long-term processes of synaptic potentiation and depression involved in memory, consciousness, and attention, he demonstrates how cells produce neural signals and regulate signal flow to enhance or impede cell-to-cell communication. Fain also addresses the relation of molecular and cellular mechanisms to evolving theories of neurological disease and addiction. Enhanced by more than two hundred illustrations, Molecular and Cellular Physiology of Neurons, Second Edition is intended for anyone who seeks to understand the fundamentals of nerve cell function, including undergraduate and graduate students in neuroscience, students of bioengineering and cognitive science, and practicing neuroscientists who want to deepen their knowledge of recent discoveries in molecular and cellular neurophysiology.